Sexual risk among Colombian adolescents: knowledge, attitudes, normative beliefs, perceived control, intention, and sexual behavior - Alexandra Morales; Pablo Vallejo-Medina; Daniella Abello-Luque; Alejandro Saavedra-Roa; Paola García-Roncallo; Mayra Gomez-Lugo; Eileen García-Montaño; Laurent Marchal-Bertrand; Janivys Niebles-Charris; Diana Pérez-Pedraza; José Pedro Espada (BMC, 2018)
Abstract Background Colombia has one of the highest rates of the human immunodeficiency virus (HIV) and pregnancies - both of which are influenced by lack of condom use -, among adolescent population in Latin America; however, the mechanisms underlying the inconsistent use of condoms in this population are poorly understood. This descriptive and cross-sectional study's purpose was to examine sexual behavior and its precursors using the theory of planned behavior (TPB) and considering gender-based differences. Another objective was to study the mediating effect of intention in the relationship between behavior precursors and condom use based on the TPB. Methods We recruited 1100 adolescents aged between 14 and 19 years old (M = 15.94, SD = 1.30, 54.4% female) from Bogotá and Barranquilla, two of the cities with highest adolescent birth rates among adolescents in Colombia. Sociodemographic variables, knowledge on HIV and other sexually transmitted infections (STIs), HIV/AIDS-related attitudes, including attitudes toward the use of condoms, normative beliefs, perceived behavioral control, behavioral intention, and sexual behavior were assessed using self-reports. All analyses were run using SPSS v25. The indirect effect of intention to explain the relationship between precursors and the use of condoms during sexual intercourse was estimated using the PROCESS v3 macro. Results Descriptive analyses suggest a high risk of contracting sexually transmitted infections and unplanned pregnancies associated to inconsistent condom use, medium-low level of knowledge about sexual health, low normative beliefs regarding peers' condom use, and a certain perceived difficulty for using condoms. Condoms are used 71% of the times they have sex, but only 22% of the participants use them consistently; girls use condoms more consistently than boys. Sexual risk characteristics differed significantly by gender. Mediation analyses indicated that condom use intention mediates the relationship between behavioral precursors and frequency of condom use, according to the TPB. Conclusions Findings provide a better understanding of sexual risk and highlight important implications for the sexual and reproductive health of adolescents. There is a need of designing and implementing protocolized sexual health promotion programs in schools with the aim of reducing sexual risk behaviors in Colombian adolescents.